The Relevance of Contemporary Islamic Education in the Thought of Syed Muhammad Naquib Al-Attas - Mush'ab Abdurrahman Shiddiq; M. Fauzan Almursyidi; Moh Zamzami Islamy (Education Reserach Center, 2026)
The findings of this study indicate that the crisis of contemporary Islamic education is fundamentally rooted in the loss of adab, which results in confusion of knowledge and value disorientation. According to Syed Muhammad Naquib al-Attas, the erosion of adab undermines the proper recognition and placement of knowledge within its hierarchical order, thereby weakening the ethical and spiritual foundations of education. The concept of ta’dib proposed by Al-Attas proves to be highly relevant as an educational paradigm that holistically integrates intellectual, spiritual, and moral dimensions. It emphasizes not only the acquisition of knowledge but also the cultivation of moral consciousness and the embodiment of ethical conduct, ensuring the harmonious integration of faith, reason, and action. Moreover, the idea of the Islamization of knowledge serves as a crucial epistemological foundation in responding to secularization and the dominance of the Western worldview within modern educational systems. By affirming that knowledge is shaped by particular metaphysical and cultural assumptions, Al-Attas calls for a critical reconstruction of educational frameworks grounded in the Islamic worldview, thereby safeguarding education from subtle forms of secularization and value fragmentation.